2019
DOI: 10.4103/jfmpc.jfmpc_324_19
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of diabetic retinopathy among patients with type 2 diabetes mellitus in primary health care in security forces hospital Riyadh, Saudi Arabia

Abstract: Background: Diabetes mellitus (DM) is a metabolic disease that is characterized by distortion in the metabolism of carbohydrates, lipids, and proteins and involves hyperglycemia. DM has different types. Several complications are associated with diabetes including diabetic retinopathy (DR). DR can further results in bad outcomes that can be avoided by early diagnosis and management. Aim: The aim of this paper is to assess the awareness and knowledge level about DR among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…[ 22 ] Older diabetic patients are more likely to have longer durations of DM, which has been correlated with better knowledge about DM complications including DR.[ 23 ] However, our current study did not provide this level of differentiation, which is considered a limitation in this study, and can be included in future studies. In addition, the current analysis showed that DM duration did not independently predict KAP as has been reported by some authors,[ 20 24 ] suggesting instead that KAP are outcomes of the interaction of multiple factors rather than one factor. Possible explanations for the high levels of KAP about diabetic eye disease among older patients include frequent interaction with health staff and past experience with DM complications including hypoglycemia and hyperglycemia.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…[ 22 ] Older diabetic patients are more likely to have longer durations of DM, which has been correlated with better knowledge about DM complications including DR.[ 23 ] However, our current study did not provide this level of differentiation, which is considered a limitation in this study, and can be included in future studies. In addition, the current analysis showed that DM duration did not independently predict KAP as has been reported by some authors,[ 20 24 ] suggesting instead that KAP are outcomes of the interaction of multiple factors rather than one factor. Possible explanations for the high levels of KAP about diabetic eye disease among older patients include frequent interaction with health staff and past experience with DM complications including hypoglycemia and hyperglycemia.…”
Section: Discussionsupporting
confidence: 66%
“…Our analysis of the association between gender and knowledge of eye disease yielded a female predominance in patients with satisfactory levels of knowledge and practice. Some of the previous studies did not find gender as a factor determining KAP of diabetic eye disease[ 18 19 24 ] or showed that males were more likely than females to be aware of DR.[ 20 ] Although there is a large body of evidence suggesting that women seek health care more than men,[ 25 26 ] our data could have been affected by the uneven gender distribution (female-to-male ratio: 1.8:1), and thus, the relationship between female gender and satisfactory KAP found in this study warrants further investigation to reach definitive conclusions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These observations are in congruence with the available literature, where the level of education is the most consistent predictor of awareness scores. 16 , 25 , 27 , 28 Interestingly, only the duration of DM and HbA1c levels were significantly associated with the prevalence of DR in our cohort. In fact, those variables are well-known predictors of DR development.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have recognised the critical role of dyslipidemia in neovascular eye diseases, including DR [6] . And available evidence suggests that lipids metabolism may play a central role in the initiation and progression of DR [7] .…”
Section: Introductionmentioning
confidence: 99%